2020
DOI: 10.1111/nicc.12507
|View full text |Cite
|
Sign up to set email alerts
|

Intensive care unit nurses' knowledge, attitudes, and perceived barriers regarding early mobilization of patients

Abstract: Background: It has been recommended that critically ill patients start mobilization as early as possible. However, the clinical utilization rate of early mobilization remains low in the intensive care unit (ICU), and respiratory therapists and nurses are the primary practitioners of early mobilization in China. Aim: The aim of this study is to investigate the knowledge, attitudes, and perceived barriers of ICU nurses regarding the early mobilization of ICU patients. Design: A descriptive and cross-sectional de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
48
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(58 citation statements)
references
References 32 publications
7
48
2
1
Order By: Relevance
“…This may have been because of an increase in the number of patients being mobilized overall, resulting in decreased frequency and duration at the individual patient level. This finding may reflect a ceiling effect because of limited staffing, a barrier also identified by Wang et al 5 The authors concluded that protocolized early mobilization is safe and feasible. Further larger trials are needed to demonstrate an effect on patient outcomes, such as length of mechanical ventilation and delirium.…”
Section: What's In This Issuementioning
confidence: 85%
See 2 more Smart Citations
“…This may have been because of an increase in the number of patients being mobilized overall, resulting in decreased frequency and duration at the individual patient level. This finding may reflect a ceiling effect because of limited staffing, a barrier also identified by Wang et al 5 The authors concluded that protocolized early mobilization is safe and feasible. Further larger trials are needed to demonstrate an effect on patient outcomes, such as length of mechanical ventilation and delirium.…”
Section: What's In This Issuementioning
confidence: 85%
“…Our first paper by Wang et al examines nurses' knowledge, attitudes, and perceived barriers to early mobilization (EM) in Chinese ICUs. 5 Using a cross-sectional electronic survey of 227 nurses, they found that more than half of the nurses surveyed had good knowledge of, and a positive attitude towards, EM. However, 51% failed to understand the population that was eligible for EM, and many (39%) still did not support routine EM for critically ill patients.…”
Section: What's In This Issuementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is promising that two studies in this edition have explored nurses' perceptions about early mobilization. Wang et al's findings show that, even though nurses had good knowledge about and positive attitudes towards early mobilization, challenges remained in implementing it in routine practice in the ICU 21 . Perhaps some strategies that we identified have been used successfully in quality improvement activities 19 could overcome the challenges identified in this paper.…”
mentioning
confidence: 82%
“…Wang et al's findings show that, even though nurses had good knowledge about and positive attitudes towards early mobilization, challenges remained in implementing it in routine practice in the ICU. 21 Perhaps some strategies that we identified have been used successfully in quality improvement activities 19 could overcome the challenges identified in this paper. Furthermore, Chaplin and McLuskey's paper in this edition demonstrated inconsistency in nurses' knowledge of early mobilization and concludes that mobilization was still deemed to be a low priority.…”
mentioning
confidence: 95%